The impact of trichoderma spp. on agriculture and their identification - Japanis, Feodora Grace; Sharmilah Vetaryan,; Naalven Kumar Kumara Raja,; Mohd Azinuddin Ahmad Mokhtar,; Elya Masya Mohd Fishal, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Fungi belonging to the genus Trichoderma were discovered in the late 18th century and they have been utilized ever since their biocontrol potential was uncovered. Trichoderma species have greatly assisted the blooming of agricultural industries due to their aggressive characteristics against plant pathogens. Their role as a biocontrol agent is owed to their mode of mechanisms: induction of the plant’s defence system, mycoparasitism, the production of secondary metabolites, and rhizosphere competence. Meanwhile, their role as a biofertilizer became evident when studies conducted hitherto showed that they could increase plant’s nutrient uptake, improve the yield of crops, enhance plant’s tolerance to external stresses, and induce the germination of seeds. Since this genus is hyperdiverse, accurate identification of them is indispensable. In the past, Trichoderma spp. were identified via their morphological characteristics. However, the emergence of molecular technology has made the identification of Trichoderma isolates more precise, explicit and rapid. Hence, this paper briefly reviews the accumulated knowledge in respect of this genus. Nevertheless, an extensive study must be done in order to explore the potential in improving the natural strains of Trichoderma.